The Women’s Social Roles in TIPITAKA: บทบาทของสตรีในด้านสังคมที่ปรากฏในพระไตรปิฎก - จันทะโชโต สุขสันต์ (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
This article states of Buddhism’s point of view on women’s social roles; by study mainly of the TIPITAKA’s details, in order for understanding of the Buddhist’s point of view on women’s equality in the Buddhist era. By studying of various datas, it was found that the women’s social-status was raised during the Buddhist’s era, and was allowed to take part in social and religious responsibilities